SPECTROCOLORIMETRIC AND ELECTROMETRIC EVALUATION OF THE INFLUENCE OF PROFESSIONAL ORAL HYGIENE IN CHILDREN OF 12 YEARS ON HARD TOOTH TISSUES AND PERIODONTAL - Reyzvikh, O.E.; Denga, A.E.; Shnayder, S.A.; Skyba, V.Ya.; Skyba, O.V. (World of Medicine and Biology, 2019)
The purpose of the work was to study the negative impact of the modern method of professional dental plaque removal using erythritol-based powder on hard tooth tissues and periodontal tissues in children 12 years old. The results obtained indicate that the proposed method did not adversely affect the hard tissues of the teeth and periodontics of 12-year-old children, which made it possible to slightly increase the acid resistance of the hard tissues of the teeth, their whiteness, electrical resistance, and decrease the yellowness of the teeth. A spectrocolorimetric assessment of the effect of occupational hygiene on the gum mucosa permeability for the dye of Schiller-Pisarev solution showed that after occupational hygiene and for 12 months of observation, the permeability of the gum mucosa remained practically unchanged, which indicates the actual absence of a negative effect of occupational hygiene on the gum barrier function.
Keywords: children; professional oral hygiene; erythritol; acid resistance of enamel; electrometric indicators; spectrocolorimetry